2023
DOI: 10.3389/fpls.2023.1145414
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy loss from dry after-ripening is associated with increasing gibberellin hormone levels in Arabidopsis thaliana

Abstract: IntroductionThe seeds of many plants are dormant and unable to germinate at maturity, but gain the ability to germinate through after-ripening during dry storage. The hormone abscisic acid (ABA) stimulates seed dormancy, whereas gibberellin A (GA) stimulates dormancy loss and germination.MethodsTo determine whether dry after-ripening alters the potential to accumulate ABA and GA, hormone levels were measured during an after-ripening time course in dry and imbibing ungerminated seeds of wildtype Landsberg erect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Dry seeds were transferred to separate microfuge tubes stored in sealed plastic storage bins in the dark at -20°C under low moisture conditions to maintain seed moisture at > 10%. Previous studies in wheat, arabidopsis, and quinoa have demonstrated that storage at -20°C is useful for preserving dormancy status at harvest maturity for short storage durations, i.e., less than 6 months, and does not to negatively impact seed germinability (Mares, 1983;Romero et al, 2018;Nelson et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Dry seeds were transferred to separate microfuge tubes stored in sealed plastic storage bins in the dark at -20°C under low moisture conditions to maintain seed moisture at > 10%. Previous studies in wheat, arabidopsis, and quinoa have demonstrated that storage at -20°C is useful for preserving dormancy status at harvest maturity for short storage durations, i.e., less than 6 months, and does not to negatively impact seed germinability (Mares, 1983;Romero et al, 2018;Nelson et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Future experiments looking to replicate this study could choose not to stagger the planting date and solely rely on storing the panicles at −20 • C after harvest, which has been shown to preserve dormancy status in quinoa [14,[60][61][62]. Our research aimed to have all the plants reach maturity by the same date to avoid differences in the post-harvest conditions, but it was logistically challenging to harvest all the plants at once.…”
Section: Discussionmentioning
confidence: 99%
“…Once seeds are shed from the parent plant, if they are stored in dry conditions, their level of dormancy drops in a process called dry after ripening. During this phase, ABA levels appear to remain high [ 40 ]. When seeds are then imbibed in water, ABA levels drop, but dormant seeds sustain higher ABA levels than those which go on to germinate [ 39 , 41 ].…”
Section: Mechanisms Regulating Variability In Seed Germination Timementioning
confidence: 99%
“…A large network of regulatory factors centres on ABA and another hormone, giberrellic acid (GA), which promotes germination. Increases in GA biosynthesis, which are triggered upon imbibition, are important for germination to occur [ 40 , 42 , 43 ]. The signalling pathways of ABA and GA converge to oppositely regulate the activity of a set of transcriptional regulators which inhibit germination.…”
Section: Mechanisms Regulating Variability In Seed Germination Timementioning
confidence: 99%